2023
DOI: 10.32942/x2xg63
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The Importance of Representative Sampling for Home Range Estimation in Field Primatology

Abstract: Understanding the amount of space required by animals to fulfill their biological needs is essential for comprehending their behavior, their ecological role within their community, and for effective conservation planning and resource management. Habituated primates are often studied using handheld GPS data, which provides detailed movement information that can link patterns of ranging and space-use to the behavioral decisions that generate these patterns. However, this data may not accurately represent an anim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 108 publications
0
2
0
Order By: Relevance
“…Our findings suggest that sampling design has a major impact on Verreaux's sifaka home range estimates and it may account for differences reported, even for the same population (e.g., Norscia et al, 2006;Rudolph et al, 2019). For example, home range estimates that rely on a minimum number of locations and ignore the span of time over which these locations were collected may be inadequate to accurately estimate home range area, as recently found for capuchins (Jacobson et al, 2023). Asymptote analyses using accumulation curves suggest that location data collected over a small temporal portion of a season is not likely to be representative of a seasonal or yearly home range; these snapshots may under-represent the total amount of space used by sifaka groups.…”
Section: Home Range Estimatesmentioning
confidence: 62%
See 1 more Smart Citation
“…Our findings suggest that sampling design has a major impact on Verreaux's sifaka home range estimates and it may account for differences reported, even for the same population (e.g., Norscia et al, 2006;Rudolph et al, 2019). For example, home range estimates that rely on a minimum number of locations and ignore the span of time over which these locations were collected may be inadequate to accurately estimate home range area, as recently found for capuchins (Jacobson et al, 2023). Asymptote analyses using accumulation curves suggest that location data collected over a small temporal portion of a season is not likely to be representative of a seasonal or yearly home range; these snapshots may under-represent the total amount of space used by sifaka groups.…”
Section: Home Range Estimatesmentioning
confidence: 62%
“…We found that the addition of temporal requirements (data collected over 4 months with at least 1 month from each season) to a minimum number of locations (n = 175) was essential for reaching asymptote yearly home range values. Jacobson et al (2023) also caution against concentrated sampling to avoid bias in home range estimation., Additionally, sample size of seasons/years accounted for large differences in the precision of group home range estimates; when data were collected over just 1-2 seasons (or years), group home range estimates had much larger confidence intervals.…”
Section: Home Range Estimatesmentioning
confidence: 99%